VZTAH INDEXU EKONOMICKÉ SVOBODY K INDEXU VNÍMÁNÍ KORUPCE - Ševčík, Radim (2007)
The aim of this bachelor work is to estimate the dependency on corruption of economic freedom. Firstly, the theoretical backgrounds of both economical phenomena are examined. Then, the relationship between the economic freedom of the World Fraser Institute and the Corruption Perceptivity Index by Transparency International is discussed, using regression techniques and correlation analysis